3D geological model of an overthrust napped structure. Hășmaș mountains, Eastern Carpathians, Romania. Issue 5 (19th October 2016) - Dumitriu, Tony-Cristian; Brânzilă, Mihai; Baciu, Dorin-Sorin
ABSTRACT: This work represents an improvement of the methodology applied in the geological study of a napped structure by approaching the fault system and the formations in a 3D volumetric space. From a geological point of view, the studied area contains two thrust nappes: the Hășmaș Nappe, which is a gravitational nappe and the Bukovinian Nappe, which is an overthrust nappe. By combining data obtained from field measurements with the bibliographic support, we performed an overview of the study area. The 3D geological model has been achieved by the interpretation and drawing of 54 geological cross sections based on preexisting geological maps and accumulated field knowledge, using GSI3D and Move3D software. By using the model, one can extract information about any point in the space occupied by it, allowing real-time visualization. Also the 3D model provides a means to accurately estimate the exact limits of the strata, giving their volumes and surfaces in the context of a possible natural reserve calculation.